Cenas desescolarizadas: arte e educação como invenção de vidas - Vinagre, Talita Alcalá (2023)
This thesis aims to think of education as an inventive experience that produces free lives. Based on this, it points out the possibilities of an elaborated education by activating body and thought as expanding forces. Based on the philosophy of difference, it highlights the hypothesis around the potential relationship between art and education to give rise to subjectivities based on freedom and autonomy through open communities bringing together singularities in a position of equality - a perspective to be forged as force line within the school itself, reinventing it as spacetime for the production of self and the potentialization of life. From this perspective, educators and students form this community of learning acting in the composition of "unschooling scenes". These scenes are drawn from the empirical-experimental field of research and explained from two educational experiences, the Ori Mirim learning community and the Art Initiation Program (PIÁ). Next, it problematizes the role of school today, especially based on Ivan Illich's (1985) critique of the institutionalization of education, questioning it as a way of adapting to society - through the disciplinarization of the bodies of children and young people, as well as through the notion of meritocracy and the consequent establishment of a system to reproduce social inequalities. Finally, it shows how the spread of this schooling critique opens room for new forms of formal education, such as homeschooling. It analyzes the ethical-political effects of the speech underpining the process of regulating homeschooling in Brazil, seeking to show what motivations are at play, especially going beyond a business mindset that emulates subjection and control